The Impact of Artificial Intelligence Adoption on Auditor Performance Efficiency with Innovation as a Mediating Variable - Isamesal, Muhammad; Ekowati, Dian (Transpublika Publisher, 2025)
The audit profession has been changed by AI, which automates tasks and improves data analysis. The success of AI in auditing depends on auditors' innovation and its impact on performance efficiency. This study investigates the influence of Artificial Intelligence (AI) Adoption on Auditor Performance Efficiency, with Innovation as a mediating variable. While prior research has established the direct impact of AI on efficiency, the mediating mechanism through Innovation remains empirically untested within an integrated framework. Employing a quantitative correlational approach, data were collected via an online survey from 185 auditors working in Public Accounting Firms (KAP) in East Java, Indonesia. The collected data were subsequently analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that AI Adoption significantly and positively influences both Auditor Performance Efficiency and Innovation. Furthermore, Innovation is also proven to significantly impact Auditor Performance Efficiency. Mediation analysis indicates that Innovation significantly mediates the relationship between AI Adoption and Auditor Performance Efficiency. These results suggest that the effect of AI Adoption on efficiency is not only direct but also substantially occurs through the enhancement of auditors' innovative capabilities. This research underscores the importance of integrating technological investments with the cultivation of an innovation culture within audit firms (KAP). The study contributes recommendations for Public Accounting Firms to optimize AI benefits through sustainable and inclusive innovation across generations.